Extracts of Tagetes minuta L. front of bacteria regarding bovine mastitis - Berguenmaier de Olanda, Gabriela; Peripolli Bevilaqua, Gilberto Antônio; Damé Schuch, Luiz Filipe; Souza Prestes, Luciana; Batista Job, Ricardo (Comunicata Scientiae, 2019)
Bovine mastitis is a problem in the context of animal health. However medicinal plants are a management strategy in agroecological production systems. In this context, the plant Tagetes minuta L. plays a leading role, due to its recognition in the popular pharmacopeia. Thus, the objective of this work was to assess the effect of hydroalcoholic extracts of T. minuta from different collection sites compared to ten bacteria related to bovine mastitis. The antimicrobial evaluation was done through the microdilution technique in syrup, in 96 well microplates in triplicate, for the determination of Minimal Bacterial Concentration (MBC) (%). In the microplates, the extracts of T. minuta and the inoculums of the bacteria were placed in addition to the growth control of the bacteria and the control of the extracts, which were incubated for 72 hours at 37°C in an oven. After this time, aliquots of 5μL of each orifice were transferred to plates containing 5% equine defibrinated blood agar and maintained in incubation for 24 hours at the same previous temperature. With this, the growth readings were performed, with the subsequent interpretation of the results by the geometric mean of the MBC (%). The results indicate that there is a difference in sensitivity to microorganisms by the extracts as a function of the collection sites and both present antimicrobial action.